2022
DOI: 10.1002/advs.202204786
|View full text |Cite
|
Sign up to set email alerts
|

Single‐Cell and Spatial Transcriptomics Decodes Wharton's Jelly‐Derived Mesenchymal Stem Cells Heterogeneity and a Subpopulation with Wound Repair Signatures

Abstract: The highly heterogeneous characteristics of Wharton's jelly mesenchymal stem cells (WJ-MSCs) may be responsible for the poor clinical outcomes and poor reproducibility of treatments based on WJ-MSCs. Exploration of WJ-MSC heterogeneity with multimodal single-cell technologies will aid in establishing accurate MSC subtyping and developing screening protocols for dominant functional subpopulations. Here, the characteristics of WJ-MSCs are systematically analyzed by single cell and spatial transcriptome sequencin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 111 publications
(111 reference statements)
1
27
0
Order By: Relevance
“…This integrated approach harnesses the biological knowledge of the candidate biomarker strategy while utilizing the technical capabilities of the high-throughput strategy to discover biomarkers associated with distinct functional subgroups in a more comprehensive and precise manner [16,[21][22][23][24]. In the realm of MSCs, with the use of prior knowledge and high-throughput technologies such as single-cell RNA sequencing (scRNA-seq), specific markers related to different functional subsets of mesenchymal stem cells can be more comprehensively and accurately mined [17][18][19][20][21][22][23][24]. Therefore, in the current review, we would discuss the MSC markers that have been identified so far.…”
Section: Msc Heterogeneitymentioning
confidence: 99%
See 3 more Smart Citations
“…This integrated approach harnesses the biological knowledge of the candidate biomarker strategy while utilizing the technical capabilities of the high-throughput strategy to discover biomarkers associated with distinct functional subgroups in a more comprehensive and precise manner [16,[21][22][23][24]. In the realm of MSCs, with the use of prior knowledge and high-throughput technologies such as single-cell RNA sequencing (scRNA-seq), specific markers related to different functional subsets of mesenchymal stem cells can be more comprehensively and accurately mined [17][18][19][20][21][22][23][24]. Therefore, in the current review, we would discuss the MSC markers that have been identified so far.…”
Section: Msc Heterogeneitymentioning
confidence: 99%
“…Among these high-throughput technologies, single-cell RNA sequencing technology (scRNA-seq) is a significant innovation in the field of MSCs that has sparked widespread interest in recent years [17][18][19][20][21][22][23][24]. By deciphering the gene expression of each individual cell within a cell population, this technique reveals the astonishing complexity of cellular diversity and heterogeneity, bringing about a revolutionary breakthrough in cellular biology research [292,293].…”
Section: Nd Generation Of Msc Maker Identification-high-throughput Ap...mentioning
confidence: 99%
See 2 more Smart Citations
“…These heterogeneities were occasionally associated with molecular categories or somatic mutations but were not exclusive (Fig. S7G-H), with possible factors, including cell-extrinsic factors 65,80 to be further investigated.…”
Section: Superfamilies Defined By Hox Gene Expression Profilesmentioning
confidence: 99%